An empirical study on impact of monetary policy on Vietnamese stock market's liquidity - Ngo, Thanh Thanh Huyen (H. : ĐHQGHN, 2020)
This study examines the effect of monetary policy on the liquidity of the Vietnamese stock market between November 2014 and November 2017 with a sample of 50 companies in the above period. Three liquidity measures including Amihud, Turnover and Zeros are used to measure the liquidity o f the market. Two major variables of monetary policy and three liquidity measures are used in the VAR model. The results show that unexpected changes in the two main variables of monetary policy have a consistent effect on liquidity in the market. In particular, the positive change in the M2 supply led to increased liquidity and positive momentum in interest rates that reduced liquidity. Shocks in industrial output have not had a consistent impact on Vietnam’s stock market. Meanwhile, the rise of inflation reduces the liquidity of the market and vice versa. Shock in the volatility of profitability reduces the liquidity of the stock market.